CHARACTERISTICS OF SARDINE FISH OIL EMULSION (Sardinella sp.) FLOUR BY-PRODUCT DURING STORAGE - Haryati, Kristina (Jurnal Perikanan Unram, 2025)
Sardine fish oil, which is mostly considered useless, is actually very beneficial because itcontains various omega-3 fatty acids, especially EPA and DHA so that fish oil is made into anemulsion product. Emulsion is a two-phase system in which small droplets of one liquid aredispersed into another liquid. The purpose of this study was to determine the characteristics ofthe best emulsion formula for 30 days of storage. The methods in this study include the stageof determining the emulsion formula, and the emulsion testing stage. In making the emulsionformula, the types of emulsifiers used were Carboxymethyl Cellulose (CMC) and lecithin witha ratio of 1: 1; 1: 2; 3: 1; and 3: 2. The tests carried out included viscosity, pH, and percentstability. The results showed that the highest viscosity, pH, and percent stability tests during 30days of storage were in formula 3: 1 and the lowest in formula 1: 2. During 30 days of storage,there was a decrease in the viscosity, pH, and emulsion stability values for all formulas. Thisfinding shows that the best emulsion formula uses CMC and lecithin emulsifiers, namely 3:1.Thus, this study shows that sardine fish oil emulsion has the potential to be developed into anemulsion product using the existing formula